Turbulent flow control using spanwise travelling wave via Lorentz forcing - Xu, Peng (2009)
Lorentz-forcing spanwise travelling wave actuation in the turbulent boundary layer has been studied in a water channel at various experimental conditions (St = 139.2, 186 and 232; T+ = 17, 42 and 82). At the Reynolds number of Reτ = 388, a maximum skin friction drag reduction of 30% is achieved in some cases, while up to 22.8% of viscous drag increase is also observed.